2001
DOI: 10.1348/014466601164740
|View full text |Cite
|
Sign up to set email alerts
|

Nationalism and patriotism: National identification and out‐group rejection

Abstract: It is argued that the differentiation between nationalism and patriotism proposed in the literature can be seen as analogous to judgments based on different types of comparisons: intergroup comparisons with other nations are associated with intergroup behaviour that corresponds to nationalism, whereas temporal or standard comparisons are linked with behaviour that corresponds to patriotism. Four studies (N = 103, 107, 96 and 105) conducted in Germany and Britain examined the hypothesis that national identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
326
3
16

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(382 citation statements)
references
References 13 publications
20
326
3
16
Order By: Relevance
“…N-I identity and values related to rejection of outgroups constituted a package and predicted both positive and negative views of Europe. The finding that The N-I identity and the related value package was better at predicting negative than positive reactions was consistent with research on the association between nationalism and outgroup rejection (Leyens et al, 2003;Mummendey et al, 2001). Furthermore, supporting the view that identities may have social-structural antecedents (Deaux & Martin, 2003), the authoritarian-nationalistic package was related to a low level of urbanization.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…N-I identity and values related to rejection of outgroups constituted a package and predicted both positive and negative views of Europe. The finding that The N-I identity and the related value package was better at predicting negative than positive reactions was consistent with research on the association between nationalism and outgroup rejection (Leyens et al, 2003;Mummendey et al, 2001). Furthermore, supporting the view that identities may have social-structural antecedents (Deaux & Martin, 2003), the authoritarian-nationalistic package was related to a low level of urbanization.…”
Section: Discussionsupporting
confidence: 80%
“…This identity was grouped with ethnocentric, authoritarian, and antisecular values, i.e. values related to rejection of outgroups (Mummendey et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piaget & Weil, 1951;Jahoda, 1962;Lambert & Klineberg, 1967;. From the perspective of evaluating the findings of these earlier studies, this may be an unfortunate omission because social-psychological research with adults has revealed that the strength of identification with an ingroup can be an important influence on attitudes towards both the ingroup and salient comparison outgroups, with there being systematic differences in the attitudes of low and high identifiers (e.g., Jetten, Spears & Manstead, 2001;Mummendey, Klink & Brown, 2001;Perreault & Bourhis, 1998;Schmitt & Branscombe, 2001). Hence, in the present study, the strength of English children's national identification was assessed in order to ascertain whether there are any changes in the strength of national identification through the course of middle childhood, at the time when their attitudes to other nations are developing.…”
Section: Introductionmentioning
confidence: 99%